Algoritma Dijkstra dan Algoritma Semut dalam Menyelesaikan Masalah Lintasan Terpendek (Studi Kasus Jaringan Transportasi Pariwisata di Pulau Lombok) - Borisman Bertinegara; Mamika Ujianita Romdhini; I Gede Adhitya Wisnu Wardhana (Universitas Islam Negeri (UIN) Mataram, 2012)
On daily life, we often travel from one place to another place another by considering the efficiency, time and cost of having the accuracy required in determining the shortest path. The determination of the shortest path will be a consideration in the decision to show the path that will be pursued. The results obtained also require speed and accuracy with the help of computers. On testing, except performed the shortest route search, the search process is also carried out comparisons between Dijkstra’s Algorithm and Ant Algorithm. Refers to a previous study by Izzat Pratama on 2011 is more focused on the development of tourism transport models with 2-dimensional , Pascal-based visualization technology and use Dijkstra's algorithm in the process of finding a route. The study that researcher developed more emphasis on comparison of the algorithms that is the Dijkstra Algorithm and Ant Algorithm. The results of this study form the shortest path between two specified nodes along the tracks and speed (running time) of both the algorithm that used. The Dijkstra’s Algorithm in solving the shortest path between a specific pair of nodes has a speed 0 second and Ant Algorithm takes much longer, which is an average 37 seconds. However of the Ant Algorithm, the resulting trajectory is more varied. Of the results obtained, it can be said Dijkstra Algorithm is more efficient in the problem of finding the shortest path in the case of transportation networks on tourism of Lombok Island.